Postoperative Complication and Depression: A Literature Review - Sendy Aditya Nugraha (Open Access Indonesian Journal of Medical Reviews, 2021)
Surgical procedure is a significant factor for patients and is associated with depression. This literature review aimed to identify depressive conditions in patients with a history of postoperative hospitalization. Depressive conditions, anesthesia, and surgery can lead to a high increase in patient morbidity and mortality. Major depressive disorder is a common complication leading to increased morbidity and mortality. Depressive disorders can cause patients to develop certain diseases that occur postoperatively, especially in patients who have malignant tumors or carcinomas that will undergo surgery. Depression is associated with cognitive impairment, which is exacerbated by postoperative events. There is evidence that postoperative pain is seriously depressing, and depression causes pain to worsen. Depression is also a strong predictor and correlates with persistent postoperative pain. In conclusion, depression can also occur in patients admitted to the intensive care unit, associated with high morbidity and mortality rates, thereby increasing the possibility of additional hospitalization costs.